Hubungan Tingkat Pengetahuan Keluarga dengan Efikasi Diri Pasien Pasca Stroke dalam Mencegah Serangan Berulang - Ni Luh Putu Thrisna Dewi; Ni Made Nopita Wati (Jurnal Akademika Baiturrahim Jambi, 2022)
Family has important role in controlling the risk factor of stroke even controlling a repeated attack. The knowledge of the family also contributes in the patient's self evication  and it leads to the patient's behavior in the prevention of repeated attack. The purpose of the research is to know the relation the family knowledge level with the post stroke patient's self evication in preventing repeated attack. The research is quantitative with descriptive correlation research design which uses cross sectional approach, measure and collected together at once in the same time. The population in this research are all the stroke patient and the family when they were visiting neurology polyclinic in one of hospital in Bali 53 people by using total sampling technique. The research found that most of the family knowledge that does not come with a low patient's self evication which are 24 people (43,3%), enough family knowledge which come with enough patient's self evication which are 17 people (32,0%) and the family which have a high knowledge most of the patient that they take care also have high stroke self evication which are 3 people (5,6%) with P value 0,000 and r = 0,765 which means there is a relative between the family knowledge with a patient self evication. The stroke patient's self evication in changing the patient behavior fixing meal pattern and life style in two adaptive direction in future.